2020
DOI: 10.1371/journal.pone.0235044
|View full text |Cite
|
Sign up to set email alerts
|

“They all laughed and asked me if I enjoyed having sex with those guys”: Exploring men’s lived experiences when reporting rape to police in South Africa

Abstract: Rape is the most demoralizing type of crime violating human rights worldwide. Research has primarily focused on children and women's experiences of rape, even though victims include men and little documentation available concerning their experiences of reporting these incidents. The study aimed to investigate men's experiences when reporting rape to the police. An Interpretative Phenomenological Analysis was used to collect and analyze qualitative data from a purposive sample of eleven men who were rape victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…3. Consultation (Buffone & Goldman, 2021;Henky, 2017;Mgolozeli & Duma, 2020;Sutama et al, 2023) Forensic psychologists provide consultation that is important in the recovery process of rape victims. Through in-depth assessment, psychologists help victims cope with trauma and move on with life by providing needed support and guidance.…”
Section: Forensic Psychology Prepares Rape Victims For Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Consultation (Buffone & Goldman, 2021;Henky, 2017;Mgolozeli & Duma, 2020;Sutama et al, 2023) Forensic psychologists provide consultation that is important in the recovery process of rape victims. Through in-depth assessment, psychologists help victims cope with trauma and move on with life by providing needed support and guidance.…”
Section: Forensic Psychology Prepares Rape Victims For Trialmentioning
confidence: 99%
“…The results showed that it is often difficult to prove rape or sexual assault, especially if there are no witnesses (Kazmi et al, 2023). The public is still not fully aware of the law, especially sexual crimes against women and children (Mgolozeli & Duma, 2020). Victims may also fear social retaliation or discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Á meðan þolendaskömm í kynferðisbrotum gegn konum tengist hugmyndinni um að konur séu að hluta til ábyrgar fyrir ofbeldinu er líklegt að í kynferðibrotum gegn körlum tengist hún frekar hugmyndum um hvað það merkir að vera karlmaður. Karlkyns þolendur kynferðisbrota geta upplifað aukna skömm vegna þeirrar mýtu að líkamlegur styrkleiki þeirra aetti að koma í veg fyrir að kona geti beitt þá ofbeldi, eða að karl sem er nauðgað af öðrum karli hljóti að vera samkynhneigður (Lysova & Dim 2020;Mgolozeli & Duma 2020;Tsui o.fl. 2010).…”
Section: Stjórnmálunclassified
“…Despite a lack of comprehensive statistics in Nigeria, evidence from several states indicates that rape incidents are rising (Izzi & Obinuch, 2016). Rape is a worldwide issue (Persson & Dhingra, 2021) and is recognised as the most traumatic experience, with harmful implications for victims and their families (Mgolozeli & Duma, 2020). It is considered a traumatic event with long-term health consequences (Olaleye & Ajuwon, 2019;Oshodi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%